Tabela de vida ecológica do minador-dos-citros, Phyllocnistis citrella stainton (Lepidoptera: Gracillariidae) - Lioni, Adriana S.R.; Cividanes, Francisco J. [UNESP] (Springer Nature, 2004)
The construction of ecological life tables is a useful tool to understand the population dynamics of insects in the field. In this work, ecological life tables were developed for Phyllocnistis citrella (Stainton) in an orchard of Citrus sinensis situated in Santa Rita do Passa Quatro, Sao Paulo State, during 2002. The occurrence of generation overlay in the field was avoided by obtaining the eggs from infestation on young citrus plants (Citrus limonia) kept under controlled conditions. The samples were taken every other day and the number of live, dead, predated and parasitized individuals were recorded. The occurrence of arthropod predators was determined through visual search on the plants of the orchard. The key factors of mortality acting on P.citrella populations were: pupae parasitism caused by Ageniaspis citricola (Logvinovskaya), action of uncertain factors on prepupae and predation of 3rd-instar larvae. The most abundant arthropod predators belonged to the families Formicidae, Chrysopidae, Coccinellidae, Reduviidae e Araneae. In two of five generations of P. citrella, approximately 4% of A. citricola pupae were hyperparasitized by Galeopsomyia fausta (LaSalle) (Hymenoptera: Eulophidae).
Ecological life table of the citrus leafminer, Phyllocnistis citrella stainton (Lepidoptera: Gracillariidae)
Keywords: Citrus sinensis; Hiperparasitism; Natural enemy; Population dynamics; Predator; Ageniaspis citricola; Araneae; Arthropoda; Chrysopidae; Citrus; citrus leafminer; Citrus x limonia; Coccinellidae; Eulophidae; Formicidae; Galeopsomyia fausta; Gracillariidae; Hexapoda; Hymenoptera; Lepidoptera; Phyllocnistis citrella; Reduviidae